ENHANCE A DESIGN SECURITY BASED ON IOT ANDROID DOOR - Ruth Chyntia Rouli Marpaung; Adi Sastra P Tarigan; Zuraidah Tharo (Sean Institute, 2023)
Conventional doors typically consist of a doorknob and keyhole for opening them. In contrast, office doors can be made more convenient. These doors will automatically open in response to a physical stimulus. For example, when someone wants to enter a room, the door will open automatically. Doors like this can be designed using automatic control systems utilizing embedded equipment such as microcontrollers. This paper discussed an automatic door system can be designed using automatic control combined with sensors and servo motors. In terms of input equipment.